Development of Simulation Scenario Model for Simulation Based Learning - Panawatthanapisuit, Supapen; Lertlum, Lamad; Tanasansutee, Chanida (Journal of Health Science of Thailand, 2019)
This study aimed to develop the simulation scenario for simulation based learning. It was divided into 3 phases. The phase 1 studied the conditions and context of simulation based learning by using semi-structured interviews and focus group discussion, analyze data with content analysis. In phase 2, a model of simulation scenario was devloped by documentation studing, data determining, scenario developing and contents approving by experts. The phase 3 involved evaluation of the results of using the scenario from 69 instructors. Data were collected by using questionnaire on knowledge related to scenario design; and t-test statistics was use to analyze the difference of pretest-posttest scores. The results revealed that every department in nursing college used simulation scenario with two aspects: (1) for teaching and learning and (2) for evaluating learning outcomes. Most instructors had experience on general situations in nursing for students to analyze for nursing cares but not for scenario design for simulation based learning which involved more factors and details; resulting in insufficient scenario which covered all learning objectives, student performances and professional competencies. The scenario model consisted of learning goals, objectives, overview and flow of simulation, learning performance measure, simulation background, facilitator guides, and script to the simulator. The outcome of simulation scenario model utilization was found to be significantly better when compared to the pretest data (t=14.02, p<0.05); and good level of satisfaction was also observed (Mean=4.51, SD=0.36). It was recommended that nursing college should organize workshops to develop the skills of instructors in designing the scenario to enable teaching and learning with more simulation based learning.